Diagnostic Accuracy of Sonazoid-Enhanced Ultrasonography for Detection of Liver Metastasis - Anas Elgenidy; Khaled Saad; Reda Ibrahim; Aya Sherif; Taher Elmozugi; Moaz Y. Darwish; Mahmoud Abbas; Yousif A. Othman; Abdelrahman Elshimy; Alyaa M. Sheir; Dina H. Khattab; Abdallah A. Helal; et al. (Medical Sciences)
Purpose: To evaluate the potential clinical role and reliability of Sonazoid-enhanced ultrasound (SEUS) as a diagnostic tool for liver metastatic lesions. Methods: An extensive literature search was conducted across five electronic databases, PubMed, Scopus, Embase, Cochrane Library, and Web of Science, from their inception up to January 2024 to identify all studies evaluating the use of Sonazoid-enhanced ultrasonography for detecting hepatic metastases. A meta-analysis was performed to assess diagnostic accuracy using the Meta-DiSc 2.0 software. Results: A total of 31 studies were included, 16 of which were eligible for meta-analysis and diagnostic test accuracy evaluation. A total of 13 studies in the meta-analysis evaluated the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) for 1347 metastatic and 1565 non-metastatic liver lesions. The pooled sensitivity and specificity for CEUS were 0.88 (95% CI: 0.82–0.92) and 0.92 (95% CI: 0.84–0.96), respectively. The combined positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were 11.89 (95% CI: 5.42–26.09), 0.12 (95% CI:0.08–0.19), and 91.99 (95% CI: 32.15–263.17), respectively. Additionally, four studies of the meta-analysis assessed the diagnostic performance of contrast-enhanced intraoperative sonography (CE-IOUS) in detecting 664 metastatic and 246 non-metastatic liver lesions. The pooled sensitivity and specificity for CE-IOUS were 0.93 (95% CI: 0.82–0.97) and 0.84 (95% CI: 0.65–0.93), respectively. The aggregated positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were calculated as 5.95 (95% CI: 2.32–15.25), 0.07 (95% CI: 0.02–0.24), and 77.68 (95% CI: 10.33–583.86), respectively. Conclusions: CE-IOUS and CEUS are reliable approaches for diagnosing liver metastatic lesions. CE-IOUS, in particular, exhibits higher accuracy in identifying liver metastatic lesions, indicating its potential effectiveness in clinical practice.